The State of the Autoregulation System of Cerebral Circulation in Patients who have Suffered A Hemispheric Stroke - Nigora Alikulova,; Janna Nazarova,; Muso Urinov,; Gulbahor Urinova, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study examines the state of the autoregulation system of cerebral circulation in patients who have suffered a hemispheric stroke. It analyzes changes in cerebral blood flow, focusing on significant alterations in the velocity and volume of blood flow in major arteries, such as the internal carotid and vertebral arteries. The findings indicate distinct differences in cerebral circulation between patients, with notable impairments in autoregulation among those with severe stroke symptoms. The results underscore the importance of assessing cerebral autoregulation to guide treatment strategies and improve outcomes in stroke rehabilitation.